Endorphin Massage on Intensity of Pain in the First Stage of Active Labour - Febry Mutiariami Dahlan; Riski Yanti; Cholisah Suralaga; Yenny Aulia (Health and Technology Journal (HTechJ), 2023)
Most maternity mothers feel pain during labor; the causes of pain in Indonesia is 16% because they experience complications, and 63% because they did not get information on childbirth preparation. Pain arises due to increased activity of the sympathetic nervous system and results in blood pressure and pulse. A midwife cannot provide analgetic in reducing pain, so complementary treatments are very helpful, one of which is endorphins massage. Massage therapy can systematically affect the skin surface, soft tissues, muscles, and ligaments. It can release of endorphin hormone that can cause muscle relaxation. This study aims to determine endorphin massage's effect on pain intensity in the first stage of active labor at Public Health Center Mampang Prapatan District, South Jakarta. This study used a quasi-experimental design with a pretest-posttest type of control group. This type involved two groups of subjects, one was treated (experimental group) with 15 samples, and the other was not treated (control group) with 15 samples. The total sample is 30 respondents. The research instrument used an observation sheet to measure pain intensity using the FLACC scale (Face, Legs, Activity, Cry, Consolability). Data analysis used the Wilcoxon signed rank test and the Mann-Whitney test. Based on the results of the Mann-Whitney test, it shows that the Assign value sig. (2-tailed) of 0.000. This means that 0,000 < 0,05, there is a significant difference between the pain intensity of the experimental group that was given endorphin massage and the control group that was not treated. There is a difference between the pain intensity in the first stage of active labor at Public Health Center Mampang Prapatan, South Jakarta. It is recommended that services apply non-pharmacological pain control methods of endorphin massage in labor.